Alternative energy using vortex-induced vibration from turbulent flows: Theoretical and analytical analysis - Zahari, M.; Dol, Sharul Sham (2014)
The global demand for continuous and eco-friendly renewable energy as alternative to fossils fuels is large and growing. One viable solution is a hydroelectric-power extraction system based on Vortex Induced Vibration (VIV) from vortex shedding in turbulent flows. The present work focus on capability of VIV phenomenon in generating alternative energy based on theoretical calculation and analytical study. In order to maximize the potential of energy generation, the effects of lock-in phenomenon and different geometries of cylinder were studied. The range of Reynolds numbers (Re) considered was within 1x104 - 3x105 and the cylinder diameters were varied between 0.02-0.06 meters. The increase of Re resulted in higher cylinder velocity thus increasing its power generation rate and efficiency. Maximum power generated was achieved for the largest diameter in a single cylinder application whilst an array system of the smallest diameter cylinder arrangement produced the highest power density. As a single unit of VIV system is insufficient to provide power supply to large application, this VIV application can be installed in multiple units of cylinders in order to generate sufficient power supply. VIV can also be integrated to the current renewable energy application system such as solar, wind and tidal energy.